Meshchera experiment - Vassiliev, Nikolai; Maslova, Irina (project baikal, 2025)
Experimental residential complexes of the last Soviet decades remain an under-explored layer in architecture and urban planning. The introduction of new construction technologies and design methods was supposed to provide a different quality of dwellings and the environment around them. The realized projects have been comprehended neither from the point of view of the construction industry, which is increasingly moving away from prefabricated reinforced concrete in modern practice, nor from the point of view of architecture, that is typology, plasticity and creating a comfortable environment. One of the latest large-scale experiments was carried out in Gorky – Nizhny Novgorod.